Contribution of the Mamluk Dynasty to Islamic Civilization 1250-1517 AD - Sulaeman Ahmad (Pustaka Digital Indonesia, 2025)
This article discusses the Contribution of the Mamluk Dynasty to Islamic Civilization 1250-1517. From the results of the study, it can be explained that the Mamluk Dynasty was a group of slaves from the Ayyubid Dynasty who were able to form a unified political elite that formed a Dynasty that adhered to the Militaristic Oligarchy system, the Mamluks were grouped into two phases, namely the Bahri Mamluks and the Burji Mamluks. The presence of the Mamluks as rivals of the Mongol troops who carried out military expansion into the Islamic region and succeeded in defeating the Mongol troops in the Battle of Ain Jalut and holding back the attack of Timur Lenk. During the 267 years of its existence, the Mamluk Dynasty was able to make many contributions to Islamic civilization including in the fields of political government, economics, education and the development of architectural art.